Management of logistics processes in cross-border e-commerce - Zhao, Qiuyang; Parfenov, Alexander Viktorovich (Vestnik of Astrakhan State Technical University. Series: Economics, 2024)
In the context of the globalization of the economy and the development of cross-border e-commerce, the importance of cross-border logistics is increasing, allowing for an effective process of product distribution. The issues of organizing transport and logistics processes during the delivery of goods within the framework of the functioning of cross-border e-commerce are discussed. The main aspects of the development of e-commerce logistics and its impact on the trading business have been studied. An analysis of the cross-border e-commerce market in Russia is carried out. It is noted that currently the global logistics industry is in an unstable environment. The main directions and trends in the development of logistics services in modern conditions are considered and the specifics of adapting the process of goods distribution within the framework of cross-border e-commerce to changes in the external environment are investigated. The distinctive features of e-commerce logistics have been studied in the context of its impact on the trading business, which allows for increased efficiency of logistics processes such as procurement, transportation, order processing, inventory and warehouse management, packaging and labeling. It has been proven that with the development of information technology and telecommunication networks, as well as increasing demand in the field of online trading, the need for effective logistics support is significantly increasing, and delivery speed is becoming increasingly important to provide quality service to consumers. The advantages of e-commerce are substantiated from the perspective of subjects of trade and logistics activities, which include the global nature of customer coverage and the convenience of inter-subject interaction, reduction of operating costs of trade and logistics activities, expanded opportunities for marketing and advertising support, increased level of automation of e-commerce logistics management processes.